A Word in Dichotomic Aspect - Sobirovich, Madrahimov Ilkhomjon (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is devoted to the problem of the role of word in the contrast of “language and speech”, the important signs of language word and speech word are identified in it.